THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER REPURCHASE INTENTION: THE MEDIATING ROLE OF CUSTOMER SATISFACTION AT CONFLUX COFFEE CLUB TOMOHON - Polakitan, Rafael; Laptian, S. L. H. V. Joyce; Gunawan, Emilia (Universitas Sam Ratulangi, 2026)
This study examines the influence of service quality on customer repurchase intention with customer satisfaction as a mediating variable at Conflux Coffee Club Tomohon. Using a quantitative approach, data were collected from 100 respondents through purposive sampling and analyzed using multiple linear regression, path analysis, and the Sobel test. The results show that service quality has a positive and significant effect on customer satisfaction, and customer satisfaction significantly influences repurchase intention. Furthermore, the Sobel test confirms that customer satisfaction mediates the relationship between service quality and repurchase intention. The findings suggest that higher service quality enhances customer satisfaction, which in turn strengthens the intention to repurchase. Keywords: Service Quality, Customer Satisfaction, Repurchase Intention,